567 Use of a risk assessment to assist farmers with osh management in ireland. (24th April 2018) - McNamara, J; Griffin, P; Phelan, J; Kinsella, J
Abstract : Introduction: In Ireland, persons at work, including self-employed farmers, are subject to the regulatory framework of the Safety, Health and Welfare at Work Act, 2005. This legislation requires the person in control of a workplace to prepare and implement a written workplace specific OSH management programme, referred to as a 'Safety Statement'. The legislation permits workplaces employing three or less workers to complete a Risk Assessment (RA) prepared under a statutory Code of Practice (COP) as an alternative to completing a Safety Statement. Following enactment of the 2005 legislation, the Irish Health and Safety Authority and Teagasc – the Irish Agriculture and Food Development Authority formed an alliance to: prepare the COP and RA; assist farmers to implement the RA, with or without half-day training, and to evaluate RA utility. This paper outlines some findings of evaluations related to RA completion and control implementation. Methods: RA documents from farmers (n=335, with training; n=135, without training) were obtained and controls specified for action assessed. Farm audits (n=94) were undertaken for farms where a RA document was obtained to assess implementation of RA controls specified and farm OSH standards. Data was analysed using SPSS. Results: The evaluation found that farmers specified, on average, 3 controls (2.94% of controls in RA) for implementation following RA completion. Farmers who completed half-day training specified 40% more controls. Farmers who implemented the controls they specified had a significantly higher percentage of farms with satisfactory OSH standards (92.1%) compared to those who did not implement controls (56.5%). Conclusion: The study concluded that completion of the RA in association with training led to more specification of controls. It also concluded that while the RA has positive utility among adopter farmers, more comprehensive approaches are needed to support its use among farmers challenged to implement OHS control measures.